Vital-dye enhanced fluorescence imaging of gastrointestinal mucosa: metaplasia, neoplasia, inflammation - Thekkek, Nadhi (2012)
BACKGROUND: Confocal endomicroscopy has revolutionized endoscopy by offering sub-cellular images of gastrointestinal epithelium; however, field-of-view is limited. There is a need for multi-scale endoscopy platforms that use widefield imaging to better direct placement of high-resolution probes. DESIGN: Feasibility Study OBJECTIVE: This study evaluates the feasibility of a single agent, proflavine hemisulfate, as a contrast medium during both widefield and high resolution imaging to characterize morphologic changes associated with a variety of gastrointestinal conditions. SETTING: U.T. M.D. Anderson Cancer Center (Houston, TX) and Mount Sinai Medical Center (New York, NY) PATIENTS, INTERVENTIONS, AND MAIN OUTCOME MEASUREMENTS: Surgical specimens were obtained from 15 patients undergoing esophagectomy/colectomy. Proflavine, a vital fluorescent dye, was applied topically. Specimens were imaged with a widefield multispectral microscope and a high-resolution microendoscope. Images were compared to histopathology. RESULTS: Widefield-fluorescence imaging enhanced visualization of morphology, including the presence and spatial distribution of glands, glandular distortion, atrophy and crowding. High-resolution imaging of widefield-abnormal areas revealed that neoplastic progression corresponded to glandular heterogeneity and nuclear crowding in dysplasia, with glandular effacement in carcinoma. These widefield and high-resolution image features correlated well with histopathology. LIMITATIONS: This imaging approach must be validated in vivo with a larger sample size. CONCLUSIONS: Multi-scale proflavine-enhanced fluorescence imaging can delineate epithelial changes in a variety of gastrointestinal conditions. Distorted glandular features seen with widefield imaging could serve as a critical ‘bridge’ to high-resolution probe placement. An endoscopic platform combining the two modalities with a single vital-dye may facilitate point-of-care decision-making by providing real-time, in vivo diagnoses.